ANALISIS KUALITAS PELAYANAN DALAM MENINGKATKAN KEPUASAN PASIEN DI PUSKESMAS LUAS KABUPATEN KAUR - Aprianty, Henny; Novica, Sentri; Dani, Rahiman (Perkumpulan Dosen Muda (PDM) Bengkulu, 2024)
This research was carried out with the aim of: 1) To analyze the quality of patients in the service system at the Luas Health Center, Kaur Regency. 2) To classify patient satisfaction with the service system at the Kaur Regency Broad Community Health Center. The type of research used in this thesis is qualitative research. This research uses descriptive case study techniques, which are carried out intensively, in detail and in depth on the research object. The data in this research was obtained from primary data and secondary data. The data collection techniques used are the observation method, interview method, and documentation method. The data analysis technique is using Data Reduction, Data Display, and Conclusion Drawing/Verification. The results of this research show that: 1). The quality of service at the Luas Health Center in Kaur Regency is seen from: service facilities (tangibles), ability to serve (reliability), speed of response (responsiveness), guarantee/certainty (assurance) and attention (emphaty) not all of which are good or quality for services in the general poly section and ER. Of the 5 (five) aspects studied, only service facilities (tangibles), ability to serve (reliability) and attention (emphaty) were not very good. The rest, namely responsiveness and quality assurance, are quite good. 2) The quality of service at the Luas Health Center in Kaur Regency is seen from: service facilities (tangibles), ability to serve (reliability), speed of response (responsiveness), guarantee/certainty (assurance) and attention (emphaty) which is good enough for the Laboratory section. Of the 5 (five) aspects studied, only service facilities (tangibles) still have deficiencies in terms of equipment for laboratories.